The effectiveness of using a combination of eggshell waste and natural zeolite as an adsorbent for treating laundry waste - Listianti, Elisa; Sutanto, Sutanto (Universitas Pakuan, 2024)
In Indonesia, the laundry industry is expanding extremely quickly. There are worries over the concentration of surfactants accumulated in the aquatic environment because the laundry industry has expanded into both large cities and rural regions, yet control over the disposal of laundry waste is still quite poor. In order to lessen surfactant waste in the aquatic environment, we must control laundry waste. Eggshells are not used to their full potential because of a lack of public understanding. In addition to figuring out the ideal composition of the optimum ratio of zeolite to eggshell that can lower detergent levels in laundry waste, this study attempts to ascertain how successful it is to combine chicken eggshells with active zeolite in decreasing laundry waste. In this investigation, two adsorbents were used as a treatment for synthetic laundry waste (LAS) and laundry waste. There are two iterations of each treatment. A 1: 50 ml sample of 1.0 g of adsorbent in 50 ml surfactant samples (laundry waste) was employed in this investigation. It then splits into five different treatments: Zeolite 1.0 g and chicken eggshell 0 g (A), zeolite 0.0 g and chicken eggshell 1 g (B). Chicken eggshell 0.3 g and 0.7 g of active zeolite (C), 0.5 g and 0.5 g of active zeolite (D), and 0.7 g and 0.3 g of active zeolite (E). The findings demonstrated that the detergent content decreased from 50.507 mg/L to P1 (A) 39.535 mg/L, P2 (B), 44.794 mg/L, P3 (C), 38.311 mg/L, P4 (D), 42.063 mg/L, and P5 (E) 37.396 mg/L. These results corresponded to an advisory capacity of A; 0.5484 mg/g, B; 0.2855 mg/g, C; 0.6095 mg/g, D; 0.4222 mg/g, and E; 0.6553 mg/g. The percentage efficiency of each treatment was determined to be 21.724%, B: 11.311%, C: 24.148%, D: 20.073%, and E: 25.959%. E saw the biggest drop, coming in at 37.396 mg/l. According to the study's findings, treating chicken eggshells has a 25.959% efficiency rate and an adsorption capacity of 0.6553 mg/g. The ideal mixture is 0.3 gr. of zeolite and 0.7 gr. of eggshell. Eggshell and natural zeolite are combined in the absorption process of LAS/SLS compounds, with a contact time of 30 minutes and a discharge rate of 8 ml/minute. ABSTRAK Di Indonesia, industri laundry berkembang sangat pesat. Ada kekhawatiran mengenai konsentrasi surfaktan yang terakumulasi di lingkungan perairan karena industri laundry telah berkembang baik di kota-kota besar maupun daerah pedesaan, namun pengendalian terhadap pembuangan limbah laundry masih sangat buruk. Untuk mengurangi limbah surfaktan di lingkungan perairan, kita harus mengendalikan limbah laundry. Cangkang telur belum dimanfaatkan secara maksimal karena kurangnya pemahaman masyarakat. Selain untuk mengetahui komposisi ideal perbandingan zeolit terhadap cangkang telur yang optimal yang dapat menurunkan kadar deterjen pada limbah laundry, penelitian ini juga berupaya untuk mengetahui seberapa sukses kombinasi cangkang telur ayam dengan zeolit aktif dalam menurunkan limbah laundry. Dalam penelitian ini digunakan dua adsorben sebagai pengolahan limbah laundry sintetik (LAS) dan limbah laundry. Terdapat dua iterasi pada setiap perlakuan. Sampel 1: 50 ml dari 1,0 g adsorben dalam 50 ml sampel surfaktan (limbah cucian) digunakan dalam penyelidikan ini. Selanjutnya dipecah menjadi lima perlakuan berbeda: Zeolit 1,0 g dan cangkang telur ayam 0 g (A), zeolit 0,0 g dan cangkang telur ayam 1 g (B). Cangkang telur ayam 0,3 g dan 0,7 g zeolit aktif (C), 0,5 g dan 0,5 g zeolit aktif (D), serta 0,7 g dan 0,3 g zeolit aktif (E). Hasil penelitian menunjukkan kandungan deterjen mengalami penurunan dari 50.507 mg/L menjadi P1 (A) 39.535 mg/L, P2 (B), 44.794 mg/L, P3 (C), 38.311 mg/L, P4 (D), 42.063 mg /L, dan P5 (E) 37,396 mg/L. Hasil ini sesuai dengan kapasitas penasehat A; 0,5484 mg/g, B; 0,2855 mg/g,C; 0,6095 mg/g, D; 0,4222 mg/g, dan E; 0,6553 mg/g. Persentase efisiensi masing-masing perlakuan ditetapkan sebesar 21,724%, B: 11,311%, C: 24,148%, D: 20,073%, dan E: 25,959%. E mengalami penurunan terbesar, yaitu 37,396 mg/l. Berdasarkan hasil penelitian, pengolahan cangkang telur ayam memiliki tingkat efisiensi 25,959% dan kapasitas adsorpsi sebesar 0,6553 mg/g. Campuran yang ideal adalah 0,3 gr. zeolit dan 0,7 gr. dari kulit telur. Cangkang telur dan zeolit alam digabungkan dalam proses penyerapan senyawa LAS/SLS, dengan waktu kontak 30 menit dan laju pelepasan 8 ml/menit.